2018
DOI: 10.1007/s00425-018-2922-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exogenous abscisic acid on morphology, growth and nutrient uptake of rice (Oryza sativa) roots under simulated acid rain stress

Abstract: Application of proper ABA can improve acid tolerance of rice roots by balancing endogenous hormones and promoting nutrient uptake. Abscisic acid (ABA) has an important signaling role in enhancing plant tolerance to environmental stress. To alleviate the inhibition on plant growth and productivity caused by acid rain, it is crucial to clarify the regulating mechanism of ABA on adaptation of plants to acid rain. Here, we studied the effects of exogenously applied ABA on nutrients uptake of rice roots under simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…After 30 days of treatment, the rice growth (including the plant height and tillers number) restored under all PMS treatments, indicating the inhibitory effect on rice growth induced by PMS can be repaired in practical weeding. The recovery of rice growth was mainly due to the widely reported self-repairing effect of rice (Liu et al, 2018;Sun et al, 2019). As shown in Figure 5C, the difference in the yield of all PMS-treated rice was not obvious.…”
Section: Evaluation Of Pms Practical Applicationmentioning
confidence: 85%
“…After 30 days of treatment, the rice growth (including the plant height and tillers number) restored under all PMS treatments, indicating the inhibitory effect on rice growth induced by PMS can be repaired in practical weeding. The recovery of rice growth was mainly due to the widely reported self-repairing effect of rice (Liu et al, 2018;Sun et al, 2019). As shown in Figure 5C, the difference in the yield of all PMS-treated rice was not obvious.…”
Section: Evaluation Of Pms Practical Applicationmentioning
confidence: 85%
“…Plants can alter their root morphology, including length, volume, and surface area, to adapt to particular environmental stressors. RGR root values can also be used to gauge healthy plant growth under stressful environmental conditions (Ju et al 2017a;Liu et al 2018b). We found that lower pH SAR , A, B, C, D) indicate a significant difference (P < 0.05, Duncan's test) among soil types under a given SAR condition.…”
Section: The Impact Of Sar and Soil Type On Root Growth And Morphologymentioning
confidence: 99%
“…Nutrient uptake through plant roots can support plant growth and environmental stress resistance (Liu et al 2018b), and changes in nutrient availability or uptake may result in growth inhibition. Acid rain can alter the ability of plant roots to absorb and utilize nutrient elements (Zhang et al 2016;Ju et al 2017a;Liu et al 2018b). Consistent with this, we found that SAR pH significantly affected J. curcas root nutrient contents.…”
Section: The Impact Of Sar and Soil Type On Root Nutrient Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that the regulatory effect of ABA on the growth of roots varies among species. For example, in rice (Oryza sativa L.), exogenous ABA increases root biomass and modifies root morphology, including density and number of adventitious roots (Liu et al 2018). By contrast, in some legume species, ABA was reported to depress the development of lateral roots (Di et al 2018;Liang and Harris.…”
Section: Changes In Sucrose and Hormone Content During Storage Root Fmentioning
confidence: 99%